2014
DOI: 10.1115/1.4027380
|View full text |Cite
|
Sign up to set email alerts
|

Finite Element Simulation of Shielding/Intensification Effects of Primary Inclusion Clusters in High Strength Steels Under Fatigue Loading

Abstract: The change of potency to nucleate cracks in high cycle fatigue (HCF) at a primary nonmetallic inclusion in a martensitic gear steel due to the existence of a neighboring inclu sion is computationally investigated using two-and three-dimensional elastoplastic finite element (FE) analyses. Fatigue indicator parameters (FIPs) are computed in the proxim ity of the inclusion and used to compare crack nucleation potency of various scenarios. The nonlocal average value of the maximum plastic shear strain amplitude i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 41 publications
1
9
0
Order By: Relevance
“…Murakami's argument is corroborated by recent finiteelement simulations in which the effects of relative orientations of primary inclusion clusters in steels under fatigue loading were investigated by Salajegheh et al [29]. Their analyses showed a reduction of nucleation crack potency due to shielding of inclusion pairs when aligned with the applied loading direction.…”
Section: Correlation With Microstructuressupporting
confidence: 68%
“…Murakami's argument is corroborated by recent finiteelement simulations in which the effects of relative orientations of primary inclusion clusters in steels under fatigue loading were investigated by Salajegheh et al [29]. Their analyses showed a reduction of nucleation crack potency due to shielding of inclusion pairs when aligned with the applied loading direction.…”
Section: Correlation With Microstructuressupporting
confidence: 68%
“…Two final studies of note are that of Przybyla et al [20] and Salajegheh et al [21]. Przybyla et al [20] used a 2D model to determine a strain-based damage parameter as a function of surface distance to a hard inclusion in the presence of an oxide layer, which this work will parallel albeit in 3D and without considering surface oxidation.…”
Section: Introductionmentioning
confidence: 99%
“…Przybyla et al [20] used a 2D model to determine a strain-based damage parameter as a function of surface distance to a hard inclusion in the presence of an oxide layer, which this work will parallel albeit in 3D and without considering surface oxidation. Salajegheh et al [21] studied the behavior of a strain-based damage parameter with respect to interaction and orientation between inclusions in 2D and orientation between inclusions in 3D; the present work will address similar inclusion interactions based on a NiTi specific microstructure. However, both Przybyla et al and Salajegheh et al used an isotopic phenomenological plasticity model rather than CP.…”
Section: Introductionmentioning
confidence: 99%
“…For example, Salajegheh et al performed finite element analysis and showed that the effect of inclusion clusters on fatigue crack initiation decreases exponentially with increasing the inclusion spacing. 9) The COV d derived in the present study would be useful for expressing the degree of clustering and assessing its effect on fatigue. On the other hand, in order to predict the fatigue life by considering the effect of inclusions, several probabilistic models that take into account the distributions of inclusion size and shape have been proposed.…”
Section: Application Of Multiscale Size Distribution To Fatigue Life mentioning
confidence: 95%
“…[4][5][6][7] Furthermore, more complex models that consider the arrangement of multiple inclusions are being examined. [8][9][10] Salajegheh et al have calculated fatigue indicator parameters using crystal plasticity simulations under different specimen sizes and inclusion sizes. 8) They have also examined stress shielding or intensifica-tion effects by changing the position of two neighboring inclusions.…”
Section: Multiscale Analysis Of Mns Inclusion Distributions In High Smentioning
confidence: 99%